Etika Berbahasa dan Komunikasi dalam Rangka Peningkatan Profesionalisme Pelayanan Publik dalam Ranah Pemerintahan - Kinanti, Revandhani Agra; Sania, Nazwa Nawal; Murena, Nur; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the application of language ethics in public service interactions to create more effective, inclusive, and professional communication. This study uses quantitative and descriptive methods to evaluate the effectiveness of public services, particularly in the communication aspect. The primary instrument in this research is a closed questionnaire designed to measure user satisfaction with service based on indicators of clarity, ease, and politeness of language used by the staff. The results of the study indicate that although the majority of people are satisfied with the communication and language ethics of health center officers, improvements are still needed, especially in politeness, empathy, and the use of inclusive language to improve the quality of service. Limitations in this study were experienced in the distribution of questionnaires such as limited time and reach in distributing questionnaires. In conclusion, this study assesses that language ethics greatly influences the quality of service. Empathetic and clear communication makes people feel appreciated, while a less friendly communication style reduces satisfaction. Service professionalism is not only measured by the speed of work, but also by interpersonal skills and cultural sensitivity